2005
DOI: 10.1186/1471-2407-5-119
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the expression of the EphB4 receptor tyrosine kinase in prostate carcinoma

Abstract: Background: The EphB4 receptor tyrosine kinase has been reported as increased in tumours originating from several different tissues and its expression in a prostate cancer xenograft model has been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…The Eph receptors are the largest family of tyrosine kinases, comprising of 15 individual members, divided into EphA and EphB classes. Recently, several studies have documented high expression of the Eph family of receptor tyrosine kinases in tumours (Stephenson et al, 2001;Berclaz et al, 2003;Wu et al, 2004Wu et al, , 2006Lee et al, 2005;Xia et al, 2005Xia et al, , 2006Kumar et al, 2006;Masood et al, 2006). Although there is limited data on the protein levels of EphB4 in cancers, only recently, data on the biological significance of this protein in tumour biology is being accrued.…”
mentioning
confidence: 99%
“…The Eph receptors are the largest family of tyrosine kinases, comprising of 15 individual members, divided into EphA and EphB classes. Recently, several studies have documented high expression of the Eph family of receptor tyrosine kinases in tumours (Stephenson et al, 2001;Berclaz et al, 2003;Wu et al, 2004Wu et al, , 2006Lee et al, 2005;Xia et al, 2005Xia et al, , 2006Kumar et al, 2006;Masood et al, 2006). Although there is limited data on the protein levels of EphB4 in cancers, only recently, data on the biological significance of this protein in tumour biology is being accrued.…”
mentioning
confidence: 99%
“…9,12,13 This hypothesis is supported by the observation that the soluble monomeric form of the extracellular domain of EphB4 receptor (sEphB4) that blocks EphrinB2 interaction with its cognate receptors, blocks bidirectional signaling and inhibits angiogenesis at sites of neovascularization in the adult. 14 -16 Human tumor tissue analysis has shown that EphB4 is overexpressed in many tumor types: breast, 17 colon, 18 -20 bladder, 21 endometrium, 22 head and neck, 23 prostate, 24,25 and ovary. 26,27 EphB4 directly supports tumor cell survival by inhibiting apoptosis in many of these cancers.…”
mentioning
confidence: 99%
“…This suggests the intriguing possibility that EphB2 may have a different role in prostate cancer compared to the related EphB3 and EphB4 receptors. Indeed, recently published data indicate that EphB4 may have a tumor-promoting role in prostate cancer (Lee et al, 2005;Xia et al, 2005). These studies, however, did not examine the effects of ephrin ligand stimulation on the tumorigenic activity of EphB4.…”
Section: Bodymentioning
confidence: 88%
“…Our hypothesis is that signaling pathways activated by EphB2, and possibly other Eph receptors, negatively regulate the malignant properties of prostate cancer cells. Importantly, since submission of this application several reports have appeared in the literature highlighting the potentially critical role of different Eph receptors in the pathogenesis of prostate cancer Lee et al, 2005;Xia et al, 2005). We compared the levels of expression of several Eph receptors and ephrin ligands in non-transformed BPH-1 prostate epithelial cells and in three well characterized prostate cancer cell lines (DU145, PC3 and LNCaP) (Fig.…”
Section: Introductionmentioning
confidence: 99%